Labor Unions and Income Smoothing - Hamm, Sophia J. W.; Jung, Boochun; Lee, Woo‐Jong (Contemporary Accounting Research, 2018)
Abstract We study labor unions, an important stakeholder group that has not been a focus of the earnings smoothing literature. We posit that managers strike a balance between sheltering resources from employees’ profit sharing demands and catering to employees’ aversion to downside risk by smoothing earnings. We then hypothesize that a strong labor union would intensify managerial incentives to smooth earnings. Consistent with our hypothesis, we find that union strength is positively associated with earnings smoothing activities through management of both accruals and R&D expenditures.